Automatic generation of a section erection planning for European shipyards building complex ships. Issue 4 (3rd May 2016) - Rose, Christopher; Coenen, Jenny
Abstract : Purpose: – The purpose of this paper is to present a method for generating a set of feasible, optimized production schedules for the erection process of compact shipyards building complex ship types. Design/methodology/approach: – A bi-objective mathematical model is developed based on the process constraints. A Pareto front of possible erection schedules is created using a the Non-dominated Sorting Genetic Algorithm II with a custom heuristic fitness function and constraint violation. Findings: – It was possible to consistently generate a wide variety of production schedules with superior performance to those manually created by shipyard planner in negligible computational time. Practical implications: – The set of optimized production schedules generated by the developed methodology can be used as a starting point by existing shipyard planners when drafting the initial erection planning for a new project. This allows the planners to consider wider variety of options in less time. Originality/value: – No other published approach for the automatic generation of optimized production schedules of the erection process is specifically tailored to the construction of complex ships.